E-Booking Building Website Based at Badan Pengembangan Sumber Daya Manusia of North Sumatera Province - Hasibuan, Ronny Ramadhan; Triase (Journal of Computer Science and Informatics Engineering, 2023)
Regarding information technology, BPSDM is not spared from the use of information technology for work purposes. E-Booking is defined as the act of making a reservation or appointment for a service via the internet. The problem found was that in the building booking process the customer had to visit the Provsu BPSDM office to find information about building bookings or make a building booking process, after that the Provsu BPSDM recorded the tenant’s personal data and ordering data in the ledger and made a report using Microsoft Excel not in real time. Therefore, a computerized mechanism is needed which is able to accommodate in providing correct and real-time information about existing buildings and details of the costs of renting the building so that it makes it easier for all parties involved. This study uses the Waterfall system development method using the PHP and MySQL programming languages. Based on the test results using blackbox E-Booking successfully designed and used properly.